The long noncoding RNA LINC15957 regulates anthocyanin accumulation in radish - Tan, Huping; Luo, Xiaobo; Lu, Jinbiao; Wu, Linjun; Li, Yadong; Jin, Yueyue; Peng, Xiao; Xu, Xiuhong; Li, Jingwei; Zhang, Wanping (Frontiers in Plant Science, 2023)
Radish (Raphanus sativus L.) is an important root vegetable crop belonging to the Brassicaceae family. Anthocyanin rich radish varieties are popular among consumers because of their bright color and high nutritional value. However, the underlying molecular mechanism responsible for skin and flesh induce anthocyanin biosynthesis in transient overexpression, gene silencing and transcriptome sequencing were used to verify its function in radish anthocyanin accumulation, radish remains unclear. Here, we identified a long noncoding RNA LINC15957, overexpression of LINC15957 was significantly increased anthocyanin accumulation in radish leaves, and the expression levels of structural genes related to anthocyanin biosynthesis were also significantly increased. Anthocyanin accumulation and expression levels of anthocyanin biosynthesis genes were significantly reduced in silenced LINC15957 flesh when compared with control. By the transcriptome sequencing of the overexpressed LINC15957 plants and the control, 5,772 differentially expressed genes were identified. A total of 3,849 differentially expressed transcription factors were identified, of which MYB, bHLH, WD40, bZIP, ERF, WRKY and MATE were detected and differentially expressed in the overexpressed LINC15957 plants. KEGG enrichment analysis revealed the genes were significant enriched in tyrosine, L-Phenylalanine, tryptophan, phenylpropanol, and flavonoid biosynthesis. RT-qPCR analysis showed that 8 differentially expressed genes (DEGs) were differentially expressed in LINC15957-overexpressed plants. These results suggested that LINC15957 involved in regulate anthocyanin accumulation and provide abundant data to investigate the genes regulate anthocyanin biosynthesis in radish.